HUBUNGAN ASUPAN SERAT MAKANAN DAN CAIRAN DENGAN KEJADIAN KONSTIPASI FUNGSIONAL PADA REMAJA DI SMA KESATRIAN 1 SEMARANG - Intan Claudina; Dina Rahayuning Pangestuti; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Functional constipation is a defecation characterized by decreased frequency of bowel movements, stiff consistency of feces, there is remaining stool and need to do extra straining when removing it. Lack of intake of dietary fiber and liquid will cause constipation. The purpose of this study is to analyze the relationship between dietary fiber intake and fluid intake with the incidence of functional constipation in adolescents in SMA Kesatrian 1 Semarang. This research design uses analytic survey type research with cross sectional approach. The research population is all students of class XI in SMA Kesatrian 1 Semarang of 289 people. Research subjects were 73 people using purposive sampling technique that is based on inclusion and exclusion criteria. Constipation events data collection using questionnaire aids, while the intake of dietary fiber and liquid using Food Frequency Questionnaires (FFQ Semi kuantitatif). Data analysis using Chi Square test. The results showed that dietary fiber intake category less than 67.1%, fluid intake category less by 67.1% and as many as 68.5% of respondents experiencing constipation. There was a relationship between dietary fiber intake with functional constipation events (p = 0,000) and fluid intake with functional constipation events (p = 0.000). It is suggested to the school to provide educational information communication (KIE) to students about nutrition education and PGS (Guidelines of Balanced Nutrition) so that the consumption of fruits, vegetables and water is further improved to achieve sufficient intake.